Prevalence of Long QT Syndrome in Children with Congenital Sensory-Neural Deafness - Ahmad Jamei Khosroshahi; Mahmoud Samadi; Shamsi Ghaffari; Akbar Molaei; Fatemeh Chakari (Journal of Ardabil University of Medical Sciences, 2021)
Background & objectives: Long QT syndrome (LQTS), congenital or acquired disorder, is characterized by a prolonged QT interval associated with syncope attacks and sudden death. Jervell and Lange-Nielsen first described LQTS in conjunction with sensory-neural congenital deafness. In long QT syndrome, the modified QT interval is greater than 440 ms and 460 ms in men and in women respectively. Acquired forms of prolonged QT are the consequence of metabolic disorders and various medications. Since the number of people with congenital deafness in the society is not low and studies in Iran about this syndrome, especially in children are limited, therefore identification of these patients by performing an ECG and simple measures, may be useful in reducing sudden death among these patients. The aim of this study was to determine the prevalence of prolonged QT syndrome in children with congenital sensory-neural deafness which undergoing cochlear implant surgery. Methods: In this study, a single-center cross-sectional observational study, all children with congenital deafness which undergoing cochlear plantation at northwest of Iran were enrolled. Patients' heart rate and QT interval were calculated using Bazett's formula. The association of long QTc with syncope and sudden death, evaluated by using Schwartz's criteria in children with long QT syndrome. Results: Of the 357 studied patients, 204 (57.1%) were male and 153 (42.9%) were female. The mean±SD of the current age of the patients was 7.15±2.93 years with a mean of 7 years. The mean±SD of QT interval in the studied patients was 291.01±26.89 ms with a mean of 280 ms. the mean±SD of the  QTc interval in the studied patients was 400.52±25.74 ms with a median of 404 ms. Frequency of Long QTc in the studied patients was 17 cases (4.8%) and long QT syndrome was 5 cases (1.4 %). Conclusion: The prevalence of prolonged QT syndrome in patients with congenital deafness in northwest of Iran in 2019 was 4.8%, and 2 cases had syncope and 3 cases had sudden death.